Innovative production machines and systems : fifth I*PROMS Virtual Conference, 6-17th July 2009 - Pham, D. T.; Eldukhri, E. E.; Soroka, A. J. (Whittles, 2010)
This collection of almost 70 papers is a focal point for access to information from researchers and industrial practitioners in the field of intelligent systems and soft computing techniques and their application in diverse areas within manufacturing.